Consumption of cowpea-based dishes in Benin: Main motives and barriers, and spatial and temporal changes - Akissoe, Lorène; Icard-Vernière, Christèle; MADODE, YANN EMERIC E.; Hemery, Youna; KPOSSILANDE, Claudia, E.; Mouquet-Rivier, Claire; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2022)
In Benin, cowpea products are commonly consumed traditional dishes. Urbanization and income changes contribute to eating habit modifications in low- and middle- income countries. Therefore, the aims of this study were (i) to identify factors influencing cowpea consumption and (ii) to document generational changes in cow- pea consumption in rural and urban areas. A Food Frequency Questionnaire, which considered nine cowpea-based dishes classified in three groups (doughnuts, stews, and mixed dishes), was filled in by 1,217 adults in Cotonou (urban area) and in Adjohoun and Allada (rural areas). Sixteen focus group discussions (n = 7–13 partici- pants/each) were also carried out. Cowpea-based dishes were consumed by 90%–95% of respondents. Socioeconomic and demographic factors had little or no influence on cowpea-based dish consumption. The main motivations for their con- sumption were health benefits and satiety provided at low cost. The main barriers to cowpea consumption, identified by participants, were preference for other foods, lack of availability as street food, and ignorance of some traditional dishes. Digestive discomfort was also identified as a factor that reduced the frequency of cowpea- based dish consumption, but not as a factor of non-consumption. Changes in cooking methods and consumption patterns were pointed out by the respondents for some of these cowpea-based dishes with the aim to reduce cooking time or improve the dish attractiveness. Our findings bring knowledge on cowpea consumption in urban and rural areas in the south of Benin that could help to develop strategies for limiting the nutritional transition-linked decrease of cowpea consumption in the future.
Keywords: consumption barriers; dietary habits; pulses; traditional dishes